Hatar män teater? - Hoogland, Rikard (Peripeti, 2012)
The paper discusses why a majority of males no longer finds it important to take part in culture, and especially visiting theatre performances. This problem is not directly addressed by the Swedish cultural policy, in spite of the cultural goals that aims to involve all. Is the politics of equality leading to less value for theatre in terms of power structures? Is the hegemonic masculinity threatened by theatre, is it seen as something feminizing?